Chromatography concepts and contrasts - Miller, James M. (Wiley, 2005)
A classic on all of the major chromatographic techniques--now fully updated. Still a popular text today, the first edition of Chromatography: Concepts and Contrasts was one of the first books to cover all of the different types of chromatography. This new Second Edition offers the latest information on the topic while preserving the clear, unified approach that has made the original a classroom favorite. Chromatography: Concepts and Contrasts, Second Edition presents the theoretical base common to various chromatographic methods, giving readers a set of general concepts for a broad understanding of the practice before moving on to discuss specific techniques. It covers gas chromatography (GC), liquid chromatography in columns (LC), and thin layer chromatography (TLC), as well as related topics such as extraction, solid phase extraction, solid phase microextraction, and mass spectrometry. The resulting text combines technical depth and comprehensiveness with accessible language and clear descriptions.